Evaluation of the interfacial shear strength between pseudoplastic NiTi shape memory alloy wires and epoxy by the pull-out method. (13th November 2015) - Spārniņš, E; Andersons, J; Michaud, V; Leterrier, Y
Abstract: The interfacial shear strength (IFSS) between nickel–titanium (NiTi) shape memory alloy wires, characterized by a nonlinear stress–strain behavior, and epoxy matrix was determined by pull-out tests. Tests were carried out at several temperatures and levels of pre-strain in the wires, to evaluate the effects of embedded wire length and of crystalline state of the alloy. The IFSS between the twinned NiTi and epoxy was estimated at 24 MPa, and found to increase to 47 MPa for completely detwinned and preloaded martensitic NiTi. This increase in IFSS values was attributed to microcracking of the superficial TiO2 layer and the resulting roughening of the NiTi wire surface.